Pengaruh Harga, Lokasi dan Pelayanan Terhadap Keputusan Pembelian di UMKM Toko Listrik - Sugiarto, Achmad Fikri Fiko; Aslamiyah, Suaibatul; Harianto, Prayudi (Universitas Muhammadiyah Gresik, 2024)
Background – UMKM (Micro, Small and Medium Enterprises) nowadays have competitors emerging to compete. To face MSME business competition, business owners must find a marketing strategy so that their business continues to survive for a long time. Objective – This research aims to determine the influence of price, location and service on purchasing decisions at UD. Pondok Benowo Indah International Branch in 2022-2023. Design / Methodology / Approach – This research uses a quantitative approach with the sample taken in the research being 96 people. This research uses data obtained from primary data sources and secondary data. Primary data sources come from questionnaires addressed to the community and interviews with UD owners. Pondok Benowo Indah International Branch.Meanwhile, secondary sources of information regarding prices can be found through books and related electronic print media, location and purchasing decisions. Findings – Price influences purchasing decisions at UD. International branch of Pondok Benowo Indah in 2022-2023. Location influences purchasing decisions at UD. International Pondok Benowo Indah branch in 2022-2023. Service has no influence on purchasing decisions at UD. International Pondok Benowo Indah branch in 2022-2023. Research Implication – In this research, the results are a useful instrument for researchers to explore further knowledge and understanding. The effect of price and location considerations can influence consumer decisions when buying goods at the UD International branch store located in Pondok Benowo Indah in increasing sales volume.